Rhizome sectioning and fertilization increase the productivity of cloudberry in natural peatlands - Bellemare, M.; Rochefort, L.; Lapointe, L. (Canadian Journal of Plant Science, 2009)
The effects of combining rhizome sectioning and in-depth mineral fertilization on cloudberry (Rubus chamaemorus L.) growth and production in a natural peat bog were determined over four growing seasons. Observed enhancements of growth and fruit production included: increases in the density of ramets and leaves from the second year; increased flower density from the third year; and increased fruit density from the fourth year. No effect on fruit size was observed. These results demonstrate that it is possible to stimulate growth and productivity of cloudberry by cultural treatments applied to natural mires.Key words: Wild berry, Rubus chamaemorus, fruit yield, rhizome sectioning, mineral fertilization, cloudberry